Modified systemic immune-inflammatory index, modified systemic inflammatory response index and hemoglobin-albumin-lymphocyte-platelet score may serve as markers for evaluating the efficacy of neoadjuvant therapy in breast cancer patients - Gan, Yuhong; Zhu, Rongkun; Li, Jinyuan; Wang, Qiuming; Meng, Xiaobin (Frontiers in Oncology, 2026)
ObjectiveTo explore the evaluation value of the modified systemic immune-inflammatory index (mSII), modified systemic inflammatory response index (mSIRI) and hemoglobin-albumin-lymphocyte-platelet (HALP) score for the efficacy of neoadjuvant therapy (NAT) in breast cancer.MethodsA total of 343 breast cancer patients who received NAT at Meizhou People’s Hospital from June 2016 to October 2023 were analyzed. Clinical and pathological data before treatment and peripheral blood detection indicators were collected. A response to NAT was defined as the achievement of pathological complete response (CR) or partial response (PR). mSII, mSIRI, and HALP score were calculated, and the receiver operating characteristic (ROC) curve analysis was used to evaluate the predictive efficacy of each indicator. The relationship between NAT efficacy and mSII, mSIRI, HALP was analyzed.Results179 patients (52.2%) showed no response to NAT, while 164 (47.8%) exhibited a response. The NAT-responsive group had a higher proportion of HER2-positive and TNBC subtypes compared with the nonresponsive group (p = 0.007). Compared with the NAT-nonresponsive group, the NAT-responsive group had significantly higher levels of mSII (p < 0.001) and mSIRI (p < 0.001), while the HALP level was notably lower (p = 0.001). The cutoff value of mSII was 2500.145 (area under the ROC curve [AUC]=0.676), while mSIRI had a cutoff of 680.92 (AUC = 0.679) and HALP had a cutoff of 33.385 (AUC = 0.600) by ROC curve analysis. Logistic regression analysis demonstrated that non-luminal subtype (odds ratio [OR]=2.059, 95% confidence interval [CI]=1.294–3.277, p = 0.002), elevated mSII (OR = 3.665, 95% CI = 2.235–6.010, p < 0.001), increased mSIRI (OR = 3.860, 95% CI = 2.350–6.338, p < 0.001), and reduced HALP (OR = 2.267, 95% CI = 1.411–3.643, p = 0.001) were independently associated with NAT efficacy.ConclusionsElevated mSII, mSIRI, and low HALP score were associated with the effectiveness of NAT in breast cancer. mSII, mSIRI, and HALP score may serve as valuable predictive indicators for the effectiveness of neoadjuvant therapy in breast cancer.